IMPROVING STUDENTS’ SPEAKING MASTERY THROUGH CULTURE-BASED LEARNING (CBL) CONTENT - Salamses, Moh. Rifal; Marhum, Mochtar; Mukrim, Mukrim; Maf'ulah, Maf’ulah (Tadulako University, 2023)
This research focuses on the use of Culture-Based Learning (CBL) as learning content to improve students' mastery of English speaking. This research aims to look at the use of Culture-Based Learning (CBL) in improving the English-speaking mastery of class VII students at MTs. Negeri Tojo Una-Una. MTs Negeri Tojo Una-una is located in the District of Ratolindo, Tojo Una-una Regency, Central Sulawesi. The population in this research were all class VII students for the 2022/2023 school year with the amount of 77 students. This research method is a quantitative method with a quasi-experimental design using a sample of students in class VII A and VII B with a total of 50 students obtained by purposive sampling technique. To collect data, this research uses tests as instruments, namely pre-test and post-test given in the form of the oral test either in groups or individually. Based on the research findings, it was concluded that the use of Culture-Based Learning (CBL) as learning content shows a significant improvement. This is shown by the percentage improvement of 44.50% in students who are members of the experimental group, while in the control group, there is only an improvement of 10.60% from the pre-test, treatment, to the post-test.